2022
DOI: 10.1257/aer.20201892
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Polarizing Effects of Persuasion: Experimental Evidence from Turkey

Abstract: I evaluate randomly varied neighborhood exposure to information campaigns regarding either executive performance, or increases in executive power, prior to a Turkish referendum on weakening checks and balances on the executive. The campaigns increased voter polarization over the referendum, and subsequently changed party affiliation in national and local elections over the next two years, leading to partisan polarization. My results suggest that, when voters disagree on whether increasing executive power is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…A previous randomized trial by Blank (1991) likewise concluded that double-blind review did not differentially affect papers authored by women and men, although sample sizes were too small to have confidence in the negative result (despite being a large study, only a small proportion of papers were by female authors). Our study is large enough, and the proportion of women high enough, that we have confidence in our conclusion that blinding of author identities does not affect gender differences in peer review outcomes.…”
Section: Double-blind Review Did Not Differentially Affect Papers By ...mentioning
confidence: 95%
See 2 more Smart Citations
“…A previous randomized trial by Blank (1991) likewise concluded that double-blind review did not differentially affect papers authored by women and men, although sample sizes were too small to have confidence in the negative result (despite being a large study, only a small proportion of papers were by female authors). Our study is large enough, and the proportion of women high enough, that we have confidence in our conclusion that blinding of author identities does not affect gender differences in peer review outcomes.…”
Section: Double-blind Review Did Not Differentially Affect Papers By ...mentioning
confidence: 95%
“…Some find that papers authored by women are rated lower or have lower acceptance rates in academic journals (Fox et al, 2019; Murray et al, 2018; Walker et al, 2015; and references therein), but others have failed to find gender differences in peer review outcomes, or have even found that papers authored by women perform better than those authored by men (Lerback & Hanson, 2017; Squazzoni et al, 2021). Other biases, such as favouring papers by authors from the same country or that speak the same language as the reviewer (Murray et al, 2018), favouring authors from higher‐income (Demarest et al, 2014; Harris, Macinko, et al, 2017; Harris, Marti, et al, 2017; Kowal et al, 2022; Saposnik et al, 2014) or English‐speaking countries (Ross et al, 2006; Saposnik et al, 2014), discriminating based on author race (Nakamura et al, 2021), favouring papers by authors that are from prestigious institutions (Blank, 1991; Tomkins et al, 2017) or with prestigious reputations (Huber et al, 2022; Okike et al, 2016), favouring authors that are senior (Pleskac et al, 2021), or disfavouring newcomers to a discipline (Seeber & Bacchelli, 2017), can all distort the quality and fairness of peer review.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the effectiveness of DA in reducing gender bias in publishing remains controversial. While in the fields of medicine and economics, no significant differences have been found between DA and SA peer review systems, with female authors achieving similar publication rates under both scenarios ( Blank, 1991 ; Cho et al, 1998 ; Justice et al, 1998 ; Mahajan et al, 2021 ), DA has been found to effectively reduce gender bias in computer science ( Tomkins, Zhang & Heavlin, 2017 ). In the EcoEvo field, DA has positively impacted the number of female authors in journals such as behavioral ecology ( Budden et al, 2008 ), but this increase in female authorship may be attributed to the overall female representation ( i.e ., relative number and proportion of publications) in the field over time ( Holman, Stuart-Fox & Hauser, 2018 ; Salerno et al, 2019 ), rather than the peer-review process per se ( Webb, O’Hara & Freckleton, 2008 ).…”
Section: Introductionmentioning
confidence: 96%
“…We therefore assume that our measure of reputation is not distorted by changes in the average number of authors.25 This requires that editors can identify authors (identities) despite the referee process being double blind. In a field experiment,Blank (1991) found that in AER's double blind referee process, about 50% of referees could correctly identify the authors. Given that many authors post preliminary versions of their papers online, we assume that, in many cases, editors can also identify the authors.…”
mentioning
confidence: 99%